2019
DOI: 10.1071/fp18098
|View full text |Cite
|
Sign up to set email alerts
|

Use of retrotransposon-derived genetic markers to analyse genomic variability in plants

Abstract: Transposable elements (TEs) are common mobile genetic elements comprising several classes and making up the majority of eukaryotic genomes. The movement and accumulation of TEs has been a major force shaping the genes and genomes of most organisms. Most eukaryotic genomes are dominated by retrotransposons and minimal DNA transposon accumulation. The ‘copy and paste’ lifecycle of replicative transposition produces new genome insertions without excising the original element. Horizontal TE transfer among lineages… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
47
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(49 citation statements)
references
References 106 publications
1
47
1
Order By: Relevance
“…It has been reported that LTR-retroelements get activated by environmental stress [48][49][50]. Therefore, in the course of genome evolution, LTR-retrotransposon activity could accumulate several variations, making them an ideal source for genome-wide molecular markers [51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that LTR-retroelements get activated by environmental stress [48][49][50]. Therefore, in the course of genome evolution, LTR-retrotransposon activity could accumulate several variations, making them an ideal source for genome-wide molecular markers [51][52][53][54].…”
Section: Introductionmentioning
confidence: 99%
“…The advent of molecular markers has offered a powerful tool to address these issues; these markers have frequently been used by ampelographers and grapevine geneticists (Cipriani et al 2010;Drabek et al 2016;De Lorenzis et al 2015). Among the many classes of molecular markers proposed in the last 20 years, a relatively new universal retrotransposon-based marker system for DNA fingerprinting, inter-primer binding sites (iPBS), was used by Kalendar et al (Kalendar and Schulman 2014;Kalendar et al 2010Kalendar et al , 2019.…”
Section: Introductionmentioning
confidence: 99%
“…Retrotransposons are ubiquitous throughout the plant kingdom and exist in vast numbers of copies in any plant genome (Kalendar et al 2019). Thus, they are a well-suited source of genetic markers (Vuorinen et al 2018;Mandoulakani et al 2015;Smykal et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The comparison of the TE's abundance between the genomes of diploids and subgenomes in polyploids is of great interest as it may help to understand the speciation after the divergence from the common ancestor and the contribution of a particular genome in polyploid formation. Different molecular techniques ranging from conventional PCR to digital PCR as well as bioinformatic approaches have been applied to study TE's polymorphisms that enable rapid and accurate identification of different TE's insertions in the genome that helps to estimate genome modifications during evolution [72]. Recently, we demonstrated different abundance of Ty3/Gypsy centromeric retrotransposon on the individual chromosomes of particular subgenomes of Th.…”
Section: Introductionmentioning
confidence: 99%
“…The abundance of transposable elements (TEs) can be assessed using different approaches [72]. The computational analysis using NGS sequencing data have been successfully applied in Triticum, Hordeum and Secale studies [27,31,56,76].…”
Section: Introductionmentioning
confidence: 99%